2020
DOI: 10.1080/1331677x.2020.1720769
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, the worst form of violence: perceived income adequacy among Croatian citizens

Abstract: The article analyses to what extent individual's socio-demographic and economic characteristics relate to citizens' perceived difficulty of living on present income. The analysis is carried out by using ordered logit and partial proportional odds (P.P.O.) model on European Social Survey (E.S.S.) data. Results confirm that individual's income can be used as an indicator of financial capacity both in general and for retirees as a focus group. Respondents in financial difficulty had to draw in a higher extent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…While qualitative analyses can help us understand the economic realities of poor older people, they typically focus on the situation in a single country. Recent quantitative survey-based analyses have shed some light on the relationship between incomes and perceptions of adequacy (Isengard and König 2021;Litwin and Sapir 2009;Palomäki 2017Palomäki , 2018Palomäki , 2019Žiković 2020), but they have done so based on only one or a few questions and among all pensioners. Palomäki (2018) found that difficulties in making ends meet are common in Central Eastern Europe and in Greece, but less frequent in Continental Europe and especially in Northern Europe.…”
Section: Previous Research On Living In Poverty and The Economic Well...mentioning
confidence: 99%
See 1 more Smart Citation
“…While qualitative analyses can help us understand the economic realities of poor older people, they typically focus on the situation in a single country. Recent quantitative survey-based analyses have shed some light on the relationship between incomes and perceptions of adequacy (Isengard and König 2021;Litwin and Sapir 2009;Palomäki 2017Palomäki , 2018Palomäki , 2019Žiković 2020), but they have done so based on only one or a few questions and among all pensioners. Palomäki (2018) found that difficulties in making ends meet are common in Central Eastern Europe and in Greece, but less frequent in Continental Europe and especially in Northern Europe.…”
Section: Previous Research On Living In Poverty and The Economic Well...mentioning
confidence: 99%
“…Previous research has shown that women, those living alone, people renting their houses, those with lower education, and those in poorer health more often have difficulties in making ends meet than men, those living as couples, owner-occupiers, the higher educated, and those in better health (Litwin and Sapir 2009;Palomäki 2017, Polvinen et al 2019. The older the person, the less they have difficulty making ends meet (Litwin and Sapir 2009;Palomäki 2018;Žiković 2020).…”
Section: Control Variablesmentioning
confidence: 99%
“…Moreover, studies on perceived financial adequacy were mostly on developed countries (Li et al, 1996;Stoller & Stoller, 2003;Litwin & Sapir, 2009). Presently, studies on perceived financial adequacy (PFA) among older persons carried out in low and middle-income countries (Gildner et al, 2016;Žiković, 2020) are still limited. It is therefore important to examine PFA in developing countries with less older people friendly infrastructure, lower income per capita and rapidly ageing population.…”
Section: Introductionmentioning
confidence: 99%
“…informal norms of behavior differ, so it is logical to expect that a single monetary policy will not suit everyone equally (Baimbridge et al, 2000;Tomas Žiković, 2020).…”
mentioning
confidence: 99%